LOCAL HISTORY AS A POPULAR GENRE OF HISTORICAL RESEARCH IN THE CAUCASUS. Book review: Khapizov ShM., Shekhmagomedov MG. Karakh in XII - beg. XX centuries (historical and ethnographic essays). Mahachkala, 2019:656 - Akopan, Ajk (History, Archeology and Ethnography of the Caucasus, 2019)
Creating a true and objective picture of the historical development of any country is impossible without identifying and studying the characteristics and uniqueness of its various regions. Thus, the study of “Local history” (regional history) is one of the ways to deepen the understanding of historical processes and to identify regional differentiation within the framework of a single historical process in Dagestan, the Caucasus and in the broader framework. For example, as Russian orientalist V. Bobrovnikov writes, “the historical ethnography of Dagestan’s villages has made a significant contribution to the development of community theory in the Caucasus and in the world” [1, p. 5]. This is one of the most important directions of development of historical science in Dagestan, which received a new impetus in the early XXI century. One of the most fundamental researches in this sphere is the recently published monograph “Karakh in XII - beginning of XX century (historical and ethnographic essays)”, on the example of which we consider this direction of historical research in Dagestan.